O problema do lixo com destino ignorado: lixo outros - Santos, Aparecida do Carmo dos (2016)
This study presents an investigative approach to the waste issue and the lack of knowledge of the people and public bodies on a type of waste called “others” with symbols 7 and trash “others” without symbolism. It comes to logistics management concepts and waste Reverse Logistics, as its relationship with the landfills and the environment. It offers a proposal regarding the non-use of such materials by companies, and suggests a knowledge management more efficient in organizations in order to mitigate the damage to the environment. This work demonstrates in images and words that kind of garbage that people take knowledge of proper disposal of it. Completed by field research, the study found, through a questionnaire and observation, that this type of waste has been increasing and little has been done to alleviate this impact to the environment. As a result of the study presents a scenario where knowledge management related to reverse logistics is required.